A Study On The Power Generation Potential Of Mini Wind Turbine In East Coast Of Peninsular Malaysia - F., Basrawi; Izwan, Ismail; Thamir Khalil, Ibrahim; Daing Mohamad Nafiz, Daing Idris; Shahrani, Anuar (2016)
A small-scale wind turbine is an attractive renewable energy source, but its economic viability depends on wind speed. The aim of this study is to determine economic viability of small-scale wind turbine in East Coast of Peninsular Malaysia. The potential energy generated has been determined by wind speed data and power curved of. Hourly wind speed data of Kuantan throughout 2015 was collected as the input. Then, a model of wind turbine was developed based on a commercial a 300W mini wind turbine. It was found that power generation is 3 times higher during northeast monsoon season at 15 m elevation. This proved that the northeast monsoon season has higher potential in generating power by wind turbine in East Coast of Peninsular Malaysia. However, only a total of 153.4 kWh/year of power can be generated at this condition. The power generator utilization factor PGUI was merely 0.06 and it is not technically viable. By increasing the height of wind turbine to 60 m elevation, power generation amount drastically increased to 344 kWh/year, with PGUI of 0.13. This is about two-thirds of PGUI for photovoltaic technology which is 0.21 at this site. If offshore condition was considered, power generation amount further increased to 1,328 kWh/year with PGUI of 0.51. Thus, for a common use of mini wind turbine that is usually installed on-site at low elevation, it has low power generation potential. But, if high elevation as what large wind turbine needed is implemented, it is technically viable option in East Coast of Peninsular Malaysia.